Fastness Improvement of a Crystalline Liquid Thermochromic Print on Cotton Fabric by the Application of Silica Nanoparticles from Rice-Husk - Jantera Sekar Tirta; Hoerudin; Ida Nuramdhani (Tekstilec, 2022)
Most commercially available thermochromic dyes are not resistant to washing and rubbing when applied to textile materials. This is due to their low affinity for fibre. The addition of silica extracted from rice husk ash using the sol-gel method was performed to improve colour fastness and maintain the stability of thermochromic dyes printed on cotton fabrics. The rice husks used in this study were derived from the Baroma rice variety with silica content in ash and silica gel of 97.05% and 99.20%. The morphological structures and particle sizes of the silica obtained were analysed using a scanning electron microscope (SEM) and particle size analyser (PSA). The particle sizes of the silica product, thermochromic dye and silica-dye mixture were 53.64–60.66 nm, 2.603 nm and 5.827 nm, respectively. The printing process of silica: the dye mixture was applied to cotton fabric in a ratio of 1:1. Fluid of silica: the dye showed good stability until the seventh day of observation. Colour fastness to washing assessed using a staining scale was better with the addition of silica than without silica, i.e. 3–4 in the first washing and 3 in the third washing. Similarly, fastness to rubbing was also better with the addition of silica, i.e. 3–4 dry rubbings and 3 wet rubbings. Moreover, the combination of silica, binder, PDMS and dye (in a ratio of 1:1:1:1) gave the best colour fastness to washing and rubbing.